Pengaruh Ekstrak Daun Kelor dan Buah Pepaya Terhadap Peningkatan Produksi Asi - Yuliasari, Yayu; Anggraeni K, Milka; Kurnia Dewi, Meinasari (YCMM, 2025)
Breast milk (ASI) is the most important and best natural food for babies. The cause of low milk production can be from poor balanced nutritional factors, mental health problems such as stress or depression so that you feel anxious, trauma after using hormonal contraceptives and breast care that is not done properly. Low milk production is also caused by a lack of stimulation of the hormone oxytocin on the first day after delivery. The impact of low milk production is that mothers do not give exclusive breastfeeding to their babies. Management of low milk production can be done by fulfilling sufficient nutrition in breastfeeding mothers. This type of research is to determine the effect of moringa leaf and papaya fruit extracts on increasing breast milk production at the Munjul Health Center in 2024. Qualitative with a case study approach. There was an increase in breast milk production in breastfeeding mothers who were given moringa leaf extracts and young papaya fruits. The administration of moringa leaf extract is 10 ml more than that given by young papaya fruits.There is an effect of giving moringa leaf extract and young papaya fruit on increasing breast milk production in breastfeeding mothers at the Munjul Health Center. It is hoped that breastfeeding mothers can implement the administration of moringa leaf extract and young papaya fruits to increase breast milk production.